Relationship between handgrip strength, anthropometric and body composition variables in different athletes - Di Vincenzo, O.; Marra, M.; Morlino, D.; Speranza, E.; Sammarco, R.; Cioffi, I.; Scalfi, L. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
Handgrip strength (HGS) is a relatively inexpensive, portable and simple functional capacity test which provides information about muscle function. In the field of sport, HGS is largely used as one of the main indicators for testing and monitoring progress in muscle power. This study aimed to evaluate the relation of HGS with both anthropometric and body composition variables in a group of male athletes compared to a control group matched for age, body weight and body mass index. Male athletes aged 17-40 years who train for a minimum of 16/18 hours per week were recruited. Anthropometry, measures of HGS and bioimpedance analysis were performed. HGS and FFM were similar between the two groups, whereas FM in both absolute and percentage values was higher (p<0.05) in controls than in athletes. On the other hand, phase angle (PhA) values clearly increased in athletes by 6.1% (p=0.008) compared to controls. In athletes FFM showed a very strong correlation with HGS (r=0.918, p=0.000), where as in controls body weight gave the best correlation (r=0.509). Additionally, multiple regression analysis showed that the main predictor of HGS was FFM in athletes and body weight in controls. Our data suggest that FFM was the main determinant of muscular function in athletes, but not in control subjects.